Microfluidic Biosensor Based on Microwave Substrate-Integrated Waveguide Cavity Resonator - Lim, Sungjoon; Park, Joong Yull; Kim, Sung-Hwan; Salim, Ahmed (Journal of sensors, 2018)
A microfluidic biosensor is proposed using a microwave substrate-integrated waveguide (SIW) cavity resonator. The main objectives of this noninvasive biosensor are to detect and analyze biomaterial using tiny liquid volumes (3 μL). The sensing mechanism of our proposed biosensor relies on the dielectric perturbation phenomenon of biomaterial under test, which causes a change in resonance frequency and return loss (amplitude). First, an SIW cavity is realized on a Rogers RT/Duroid 5870 substrate. Then, a microwell made from polydimethylsiloxane (PDMS) material is loaded on the SIW cavity to observe the perturbation phenomenon. The microwell is filled with phosphate-buffered saline (PBS) solution (reference biological medium). To demonstrate the sensing behavior, the fibroblast (FB) cells from the lungs of a human male subject are analyzed and one-port S-parameters are measured. The resonance frequency of the structure with FB cells is observed to be 13.48 GHz. The reproducibility and repeatability of our proposed biosensor are successfully demonstrated through full-wave simulations and measurements. The resonance frequency of the FB-loaded microwell showed a shift of 170 MHz and 20 MHz, when compared to those of empty and PBS-loaded microwells. Its analytical limit of detection is 213 cells/μL. Our proposed biosensor is noncontact and reliable. Furthermore, it is miniaturized, inexpensive, and fabricated using simple- and easy-design processes.